HBx triggers either cellular senescence or cell proliferation depending on cellular phenotype. Issue 2 (28th August 2015) - Idrissi, M. E.; Hachem, H.; Koering, C.; Merle, P.; Thénoz, M.; Mortreux, F.; Wattel, E.
Summary: Replicative senescence is a hallmark of chronic liver diseases including chronic hepatitis B virus (HBV) infection, whereas HBV‐encoded oncoproteins HBx and preS2 have been found to overcome senescence. HBx possesses a C‐terminal truncation mainly in hepatocellular carcinomas but also in noncancerous liver tissues. Here, by cell counting, BrdU incorporation, MTT proliferation assay, cell cycle analysis, SA‐ β gal staining and Western blotting in primary and malignant cells, we investigated the effect of HBx C‐terminal mutants on cellular senescence. HBx C‐terminal mutants were found to trigger cellular senescence in primary MRC5 cells, and malignant liver cells Huh7, and SK‐Hep1. In contrast, these mutants promoted the proliferation of HepG2 malignant liver cells. The pro‐senescent effect of HBx relied on an increased p16 INK4a and p21 Waf1/Cip1 expression, and a decreased phosphorylation of Rb. Together, these results suggest that the two main variants of HBx present in HBV‐infected liver possess opposite effects on cellular senescence that depend on the phenotype of infected cells.